Developing of character science teaching tools integrated with the value of Qur'an for junior high school students - Irwansyah, Muhammad; Perkasa, Magfirah; Muchlis, Muchlis; Bakhtiar, Bakhtiar; Azmin, Nikman (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2021)
The curriculum of 2013 places spiritual attitudes as the first competencies fromcore competencies and social attitudes as the second. This indicates that aspiritual and social attitude is needed to survive in the 21st century. Therefore, thisstudy was held with the aim to develop science teaching materials with integratedcharacter of the Qur'anic verses that valid and effective criteria. The type ofresearch that used in this research is adapted from Thiagarajan’s developingmodel which focused on defining, designing, and developing stages. Theinstruments used are validation sheets for expert judgement and student responsequestionnaires to collect spiritual character of the students. Based on the resultsof the study, the science teaching materials with Islamic character interpretationsmeet the valid criteria with the validity of RPP = 3.37, modules = 3.23 and LKS =3.51. Meanwhile, based on the results of limited trials, it can be concluded that thestudents' responses to science teaching materials with integrated character of theQur’anic verse are in the positive and very positive category.